The influence of intestinal dysbiosis on skin aging (Research, Society and Development, 2024)
A balanced microbiota actively works in favor of the host's homeostasis, contributing to its health. Intestinal dysbiosis is an imbalance between the phyla (pathogenic and non-pathogenic) existing in the intestinal microbiota, which damage intestinal mucosa and disrupt intestinal junctions, causing a dysfunction in the absorption of substances in the intestinal lumen. Dysbiosis accentuates the aging process, causing several disorders throughout the body, including the integumentary tissue. Objective: to evaluate the influence of intestinal dysbiosis on the skin aging process. Methodology: a bibliographical review will be carried out, selecting articles (2003-2024) in Portuguese, English and Spanish. The databases used are SCIELO, PubMed, CAPES Periodicals, LILACS and MEDLINE. Discussion: several studies support the link between a state of intestinal dysbiosis and different types of inflammatory diseases. Maintaining a balanced diet including a good variety of fibers, in addition to the consumption of probiotics, synbiotics and postbiotics seems to be a viable alternative to improve the condition of dysbiosis and reestablish the homeostasis of the intestinal mucosa. Final considerations: Human exposure to bad eating habits, associated with genetic factors, activates the inflammasome, causing health problems and the nutritionist plays a fundamental role in the return of previously lost homeostasis.